Aeromicroflora and Indoor Air Quality: A Narrative Minireview of Sources, Pollutants, and Health Implications (Romanian Biotechnological Letters, 2025)
Indoor air quality has become a major concern in recent decades, given its strong influence on public health and well-being, as people spend the majority of their time indoors. Among the biological components of indoor air, aeromicroflora represents a critical indicator, reflecting both environmental conditions and human activity. This review summarizes the current state of knowledge regarding aeromicroflora in educational and administrative buildings, with a focus on microbial diversity, sources of contamination, health risks, and methods of monitoring and control. Special attention is given to bacteria and fungi as the predominant groups of airborne microorganisms, their potential pathogenicity, and their role as indicators of hygiene and ventilation efficiency. Moreover, the article focuses on highlighting the population categories most affected, such as children, elderly individuals, and those with pre-existing conditions or weakened immune systems. Exposure to microbiological air pollutants has been associated with a wide range of adverse health outcomes, from allergic reactions and respiratory problems to chronic inflammatory conditions.Furthermore, integrating recent findings, the review aims to provide a comprehensive perspective on the implications of aeromicroflora for environmental health, while also outlining future directions for research and practical interventions in indoor spaces. Addressing these challenges is essential for reducing health risks and ensuring safer indoor environments.
Keywords: aeromicroflora; indoor air quality; educational buildings; administrative buildings; bioaerosols; microbial contamination; public health